A new genus of the subfamily Hybrizontinae (Hymenoptera: Ichneumonidae) from Japan - Hisasue, Yu; Konishi, Kazuhiko (Zootaxa, 2019)
Neohybrizon gen. nov. is described from Japan (type species: Neohybrizon mutus sp. nov.). This new genus is characterized by much reduced mouth parts, long mesoscutum, absence of epicnemial carina, depressed posterocentral area of mesoscutum, slender stigma, short RS+M of fore wing, entirely straight M of fore wing, slender hind wing, long hind femur which is over 5.5 × as long as trochanter, and using the ant Myrmica kotokui Forel, 1911 as its host. A key to genera of Hybrizontinae is also provided.